GERAKAN POLITIK SYIAH-SUNNI DI DESA KARANG GAYAM DAN DESA BLU’URAN SAMPANG MADURA - Hodari, Hodari (Jurnal Review Politik, 2015)
This research explored about Syiáh-Sunni political action in Karang Gayam and Blu’uran, Sampang-Madura: Tajul Muluk political action is covored under IJABI goverment which was built as low foundation to cover Ahlulbait. The enlargement of Syiáh in Karang Gayam have been in to neighbour village, Blu’uran. Till many people become the follower of Syiah. The strategy deployment of Shi'ism in Karang Gayam is the humanitarian approach through material assistance to communities in need . So there is sympathy to figure Tajul Muluk , and ultimately lead to people easily accept new teachings were introduced, although the teaching is different from the teachings that they can understand so far. However, after a warning Birth of the Prophet, shifted into a political movement by the violent conflict that occurred in the of Karang Gayam village